Комплексный анализ морфологических признаков представителей рода Lymnaea подродов Corvusiana и Stagnicola (Pulmonata, Lymnaeidae) - Гарбар, А.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
Проведен комплексный анализ конхологических и анатомических характеристик 2 видов подрода Corvusiana и 4 видов подрода Stagnicola. Показано, что количественные признаки раковины и половой системы имеют ограниченное диагностическое значение на уровне вида и секции. В частности, не выявлено достоверных различий между L. turricula Held (sensu Pirogov et Starobogatov, non Jackiewicz) и L. atra Schrank — видами, относимыми к разным секциям. Наиболее надежным комплексом признаков для идентификации исследованных видов является соотношение высоты последнего оборота раковины к ее высоте в совокупности с анатомическими характеристиками. Однако и в этом случае морфологические дистанции между некоторыми видами лишь незначительно превышают межпопуляционные. В то же время, подтверждается обособленнось L. vulnerata Kuster, sensu Pirogov et Starobogatov (=L. occulta Jackiewicz) от других видов подрода Stagnicola. Complex analysis of the conchologycal and anatomical characteristics of 2 species of the subgenus Corvusiana and 4 species of the subgenus
Stagnicola based on Bonferroni test and discriminant analysis has been done. Quantitative characters of
the shell and reproductive system were shown to have limited diagnostic value on the level of species
and sections. In particular, no significant differences in the studied characters were found between L.
turricula Held (sensu Pirogov et Starobogatov, non Jackiewicz) and L. atra Schrank – species assigned
to different sections. The most reliable combination of characters for identification of the investigated
species is the ratio of the height of the last whorl of shell to its height taken together with the anatomic
characteristics. However, even in this case morphological distance between some species only slightly
exceeded inter-populational distances. At the same time, distinctness of L. vulnerata Kuster, sensu Pirogov et Starobogatov (=L. occulta Jackiewicz) from the other species of Stagnicola has been proved.